The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.701412
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Principal Working Memory Features in Generalized, Panic, and Social Anxiety Spectrum Disorders

Abstract: Anxiety spectrum disorders are characterized by excessive and uncontrollable worrying about potential negative events in the short- and long-term future. Various reports linked anxiety spectrum disorders with working memory (WM) deficits despite conflicting results stemming from different study approaches. It remains unclear, however, how different anxiety spectrum disorders such as generalized anxiety disorder (GAD), social anxiety disorder (SAD), and panic disorder (PD), differ in WM function. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In general, the data shows a highly significant correlation among all variables in this article. As expected, these results support the findings revealed in the previous literature, which indicate that there is a positive, direct association between students' implicit theory, their academic performance, and different types of intelligence (Rammstedt and Rammsayer, 2000;Blackwell et al, 2007;Chen and Wong, 2015;Alesi et al, 2016;Abushalbaq et al, 2021). Therefore, it is not just general intelligence and performance that is positively associated with incremental views of intelligence, but also other types mentioned this study.…”
Section: Discussionsupporting
confidence: 92%
“…In general, the data shows a highly significant correlation among all variables in this article. As expected, these results support the findings revealed in the previous literature, which indicate that there is a positive, direct association between students' implicit theory, their academic performance, and different types of intelligence (Rammstedt and Rammsayer, 2000;Blackwell et al, 2007;Chen and Wong, 2015;Alesi et al, 2016;Abushalbaq et al, 2021). Therefore, it is not just general intelligence and performance that is positively associated with incremental views of intelligence, but also other types mentioned this study.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the study by Klein and Schwartz (1979) also found no significant gender differences in memory performance after training in sequential auditory memory. Similarly, recent studies have shown no gender differences in working memory performance (Hirsch et al, 2019) or in the effects of working memory training on cognitive performance (Abo Hamza and Helal, 2021;Abushalbaq et al, 2021;Liu et al, 2021).…”
Section: Lack Of Gender DI Erencesmentioning
confidence: 85%
“…This notion has a substantial effect on both the instructor and the learner (Trinidad, 2020). Modern cognitive theory emphasizes the interrelation of attention, perception, working memory, and longterm memory in education (Chang et al, 2019;Cicekci and Sadik, 2019;CortĂ©s Pascual et al, 2019;Lodge and Harrison, 2019;Abo Hamza and Helal, 2021;Abushalbaq et al, 2021;Berkowitz et al, 2022). Attention serves as the primary cognitive filter for external inputs, impacting perception and learning (Lodge and Harrison, 2019).…”
Section: Cognition and Memory In The Context Of Educational Psychologymentioning
confidence: 99%
See 2 more Smart Citations